A Review of the Incidence, Manifestation, Predisposing Factors, and Management of Recurrent Pediatric Inguinal Hernia - Koivusalo, Antti I. (European Journal of Pediatric Surgery, 2017)
Recurrent pediatric inguinal hernia is relatively rare. In a large series, the recurrence rates vary from 0.3 to 1.2%. In a university hospital with surgical service for a wide spectrum of sick pediatric patients, the real recurrence rate may be 3 to 6%. Recurrence manifests typically 6 months after first repair. Current evidence indicates that recurrence rates in open and laparoscopic repair are similar. Laparoscopic repairs are, however, still performed by a minority of skilled pediatric surgeons, whereas the majority of pediatric surgeons rely on open repair not least because of the assumed lower risk of recurrence. After repair of an indirect hernia, the majority of recurrences (97%) are indirect, whereas in rare cases the recurrence turns out to be a formerly undiagnosed direct or femoral hernia. In Children's Hospital of Helsinki, Finland, recurrence rate from 2012 to 2016 was 2.8% and operations for recurrent hernias comprised 3.3% of the total. From 1991 to 2017, a total of 130 operations for recurrent hernias were performed with open inguinal approach (n = 75, 58%), laparoscopy (n = 49, 38%), and laparotomy (n = 4, 4%). One teenage patient underwent a Lichtenstein Prolene net repair. A recurrent inguinal hernia can be repaired either with an open or laparoscopic approach. In laparoscopy, the nature of the recurrent hernia can be clarified and an immediate repair performed either by laparoscopic or open technique. In expert hands new laparoscopic techniques using muscular arch, lateral umbilical ligament, iliopubic tract, and division of the sac may be an alternative to a simple purse-string closure.
Keywords: pediatric inguinal hernia; recurrent hernia; open hernia repair; laparoscopic hernia repair